2018
DOI: 10.1038/s41563-018-0081-x
|View full text |Cite
|
Sign up to set email alerts
|

Electron–phonon interaction in efficient perovskite blue emitters

Abstract: Low-dimensional perovskites have-in view of their high radiative recombination rates-shown great promise in achieving high luminescence brightness and colour saturation. Here we investigate the effect of electron-phonon interactions on the luminescence of single crystals of two-dimensional perovskites, showing that reducing these interactions can lead to bright blue emission in two-dimensional perovskites. Resonance Raman spectra and deformation potential analysis show that strong electron-phonon interactions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

33
674
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 523 publications
(731 citation statements)
references
References 42 publications
33
674
3
Order By: Relevance
“…2D perovskites, where bulky organic layers and inorganic layers are alternately and periodically arranged, feature natural quantum-well structures. [20,21] In these cases, severe structural distortion of metal halide octahedra is a common feature because of the size mismatch between organic and inorganic components, which results in potential fluctuations. [14][15][16] However, low photoluminescence quantum yields (PLQYs, typically < 1%) of 2D perovskites at room temperature is a bottleneck to achieving high-performance LEDs.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…2D perovskites, where bulky organic layers and inorganic layers are alternately and periodically arranged, feature natural quantum-well structures. [20,21] In these cases, severe structural distortion of metal halide octahedra is a common feature because of the size mismatch between organic and inorganic components, which results in potential fluctuations. [14][15][16] However, low photoluminescence quantum yields (PLQYs, typically < 1%) of 2D perovskites at room temperature is a bottleneck to achieving high-performance LEDs.…”
mentioning
confidence: 99%
“…This quantum-well structure is regarded as promising LED emitters for decades. [22,23] Such fluctuations of potential within an inorganic layer of perovskite sometimes, but not always, [20,21] slow the diffusion of carriers or excitons, and consequently induce self-trapped excitons (STEs), which represents a type of bound states for efficient radiative recombination. [17] The low PLQYs may be attributed to insufficient confinement of Wannier type excitons within the inorganic layers [18] as suggested by the long charge-carrier/exciton diffusion length (60 nm).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Following a study of the electron‐phonon interaction effects on luminescence in 2D perovskites, Gong et al suggested in a recent work that reduction of the interactions was one viable way to create strong blue light emission . Three structures with organic cations were discussed; of these structures, C4 (CH 3 (CH 2 ) 3 ) and PhC2 (phenyl C 6 H 5 −(CH 2 ) 2 ) crystals showed sharp blue emissions, while the Ph (phenyl C 6 H 5 ) crystal was characterized by a broadband white light emission.…”
Section: Novel Spin‐related Physical Effects Arising From Hopsmentioning
confidence: 99%
“…However, by using the excellent PL properties of HOPs, many blue LEDs have been proposed. In 2018, research revealed that strong electron‐phonon interactions reduce the PL . Based on this principle, researchers determined that the molecules in the brightest materials show the lowest and most rigid motions.…”
Section: Applications Of Hop Spin‐related Optoelectronic Devicesmentioning
confidence: 99%